The Son - Meyer, Philipp 1974- (New York, NY : Ecco, 2017)
Comanche Indian captive Eli McCullough must carve a place for himself in a world in which he does not fully belong--a journey of adventure, tragedy, hardship, grit, and luck that reverberates in the lives of his progeny.
Keywords: Indian captivities -- Fiction; Comanche Indians -- Fiction; Fathers and sons -- Fiction; Families -- Fiction -- Texas; Texas -- Fiction; Epic fiction; Western fiction